Post-Traumatic Intraparenchymal Renal Hemorrhages: Correlation between CT and DSA Vascular Findings for Superselective Embolization Procedures - Francesco Giurazza; Andrea Contegiacomo; Fabio Corvino; Alberto Rebonato; Davide Castiglione; Stefano Palmucci; Raffaella Niola; Antonio Basile (Diagnostics, 2021)
Background: This study aims to investigate the correlation between computed tomography (CT) and digital subtraction angiography (DSA) findings in patients affected by acute post-traumatic intraparenchymal renal hemorrhages and evaluate their conservative management with superselective embolization. Methods: This retrospective multicenter analysis focuses on patients affected by renal bleedings detected by contrast-enhanced CT and treated with superselective endovascular embolization. CT findings were compared to DSA. Embolization procedural data were analyzed and renal function was evaluated before and after the intervention. Results: Twenty-seven patients were retrospectively evaluated in one year. Compared to DSA, CT showed 96.3% diagnostic accuracy in terms of hemorrhage recognition; concerning the type of vascular lesion, there was discrepancy between CT and DSA in five cases. The technical success rate of embolization was 100%, while primary clinical success was 88.9%. The inferior parenchymal third was the most frequent site of renal injury. Microcoils were the most adopted embolics. Renal function did not change significantly before and after embolization. Conclusions: CT has elevated diagnostic accuracy in detecting post-traumatic intraparenchymal renal hemorrhages; in a small percentage, the type of vascular lesion may differ from the findings observed at DSA. In this scenario, superselective embolization presents high clinical success with a low complication rate.